Extra Virgin Olive Oil Extracts of Indigenous Southern Tuscany Cultivar Act as Anti-Inflammatory and Vasorelaxant Nutraceuticals - Luca Pozzetti; Francesca Ferrara; Ludovica Marotta; Sandra Gemma; Stefania Butini; Mascia Benedusi; Fabio Fusi; Amer Ahmed; Serena Pomponi; Stefano Ferrari; Matteo Perini; Anna Ramunno; et al. (MDPI AG, 2022)
Extra virgin olive oil (EVOO) is the typical source of fats in the Mediterranean diet. While fatty acids are essential for the EVOO nutraceutical properties, multiple biological activities are also due to the presence of polyphenols. In this work, autochthonous Tuscany EVOOs were chemically characterized and selected EVOO samples were extracted to obtain hydroalcoholic phytocomplexes, which were assayed to establish their anti-inflammatory and vasorelaxant properties. The polar extracts were characterized via 1H-NMR and UHPLC-HRMS to investigate the chemical composition and assayed in CaCo-2 cells exposed to glucose oxidase or rat aorta rings contracted by phenylephrine. Apigenin and luteolin were found as representative flavones; other components were pinoresinol, ligstroside, and oleuropein. The extracts showed anti-inflammatory and antioxidant properties via modulation of NF-κB and Nrf2 pathways, respectively, and good vasorelaxant activity, both in the presence and absence of an intact endothelium. In conclusion, this study evaluated the nutraceutical properties of autochthonous Tuscany EVOO cv., which showed promising anti-inflammatory and vasorelaxant effects.